FAKTOR-FAKTOR YANG MEMPENGARUHI KEBUTUHAN MODAL KERJA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sitompul, Johari; Ndruru, Fiktor (JURNAL NERACA AGUNG; Vol 10 No 1 (2020): MARET, 2020)
This study aims at determining the effect of leverage, profitability, both simultaneous and partial company size on working capital requirements in manufacturing companies in the basic and chemical industry sub-sectors on the Stock Exchange in 2016-2018. The population in this study amounted to 48 companies with a sample of 14 companies. This data collection technique uses a purposive sampling technique that is sampling using certain criteria, namely: companies manufacturing basic and chemical sub-sectors listed on the Indonesia Stock Exchange in 2016-2018 and not experiencing losses during the study period in 2016-2018. Data was analyzed by using Multiple Linear Regression Analysis. The analysis proves partially leverage does not have a significant effect on working capital requirements, because the value of t count < t table (0.973 ˂ 2.024), and the t-test sig has a result greater than 0.05 (0.337 ˃ 0.05). Profitability has a negative and significant effect on working capital requirements because the t-value ˃ t table (-3,200 ˃ 2,024), and in the t-test sig is smaller than 0.05 (0.003 ˂ 0.05). The size of the company has no significant effect on the need for working capital with t ˂ t table (-0.155 ˂ 2.024), and the t-test sig is greater than 0.05 (0.878 ˃ 0.05). F test results explain that the DER, ROA, and UP variables simultaneously have a significant effect on working capital requirements because the F count value is 4.088 while the F table is 2.850, so the F count ˃ F table (4.088 ˃ 2.850). Determination coefficient test results are 0.184 or 18.40% explains that the DER, ROA and UP variables simultaneously have a significant effect on the variable needs of working capital, 18.40% changes from the variable needs of working capital, while the remaining 81.60% is caused by other variables Outside this research is capital structure and business risk.